PHENOMENON OF SEXUAL BEHAVIOR IN ADOLESCENTS IN KARANG TARUNA BANTAENG DISTRICT - Hijriah (Jurnal Mitrasehat, 2019)
In adolescence curiosity about sexual problems is very important in the formation of new relationships that are more mature with the opposite sex. This research was carried out with the aim of obtaining in-depth information about the Phenomenon of Sexual Behavior in Youth Youth, the result of adolescent sexual behavior, as well as forms of prevention of sexual behavior in adolescents in Bantaeng district. The type of research used is qualitative with a descriptive approach. Data collection techniques use Observation, Interview, and Documentation, while data analysis techniques use qualitative descriptive with stages of data reduction, presentation, and conclusion. The results of this study indicate that there is some background information about the occurrence of sexual behavior, namely the gadgad factor, the emergence of smartphones that provide freedom of social media and providers that provide low-cost social media services, clearly causing adolescents to forget the social boundaries they should know. Factor lack of knowledge, One of the problems of adolescents if lack of pranika sexual knowledge is unwanted pregnancy, unsafe abortion and also venereal disease. Peer factors are peer groups as places of interaction have a role for social life and adolescent education. Adolescent free association is one form of perilku form which deviates "Free" in question is to exceed the existing eastern boundary norms. It is often this kind of promiscuity that we often hear both within and outside the mass media. As for the form of prevention of sexual behavior, there must be good cooperation with related parties on how to improve the quality of knowledge about the impact of sexual behavior, so that the problem of lack of knowledge can be reduced. Curiosity is a turbulent feeling that can arouse people's curiosity. The curiosity usually develops when you see your own state or interesting surroundings.